(untitled) - Bennett, Arnold (Đồng Nai, 2009)
Arnold Bennett is famous for his stories about the Five Towns and the people who live there. They look and sound just like other people, and, like all of us, sometimes they do some very strange things. There's Sir Jee, who is a rich businessman. So why is he making a plan with a burglar? Then there is Toby Hall. Why does he decide to visit Number 11 Child Row, and who does he find there? And then there are the Hessian brothers and Annie Emery - and the little problem of twelve thousand pounds.
Keywords: English language,Short stories,Ngôn ngữ tiếng Anh,Truyện ngắn; Readers,Người thích đọc sách